(untitled) (Journal of Atomic and Molecular Sciences, 2013)
A scheme for generation of W state via distant cavities is presented. Employing resonant interactions between atoms and cavities, choosing different initial states, we can obtain non-maximally and maximally entangled states. In addition, our scheme could be easily generalized to generate N-atom W state. In contrast to the original scheme, our scheme is insensitive to the atomic spontaneous emission and cavity decay, it made the schemes more easily realize on experiments.